Pelatihan Apoteker Cilik dan DaGuSiBu bagi Siswa SDN Losari di Singosari, Kabupaten Malang - Atmadani, Rizka Novia; Hidayati, Ika Ratna (Jurnal Pengabdian UNDIKMA, 2020)
The purpose of this service activity is to introducing medicine from early age in order to introduce pharmacists and medicine to elementary school students. The lack of knowledge about medicines in the community begins with the provision of knowledge from an early age to elementary school students because they will later become adolescents and reduce drug abuse in the community as frequently happens to high school students or college students. The method of these activities is carried out by means of online learning using several platforms, including: class whatsapp group, google form, and youtube link. Before being given the material, a pretest and posttest was admitted at the beginning and end of the activity. There are two materials provided, first, introducing Pharmacist Profession and education for DaGuSiBu. The participants of this activity were elementary students of grade 4,5 and 6 SDN Losari. In addition, this service is expected to motivate students to have awareness and be able to supervise other classmates for practicing medicines properly.The results was found that the students received education related to the Pharmacist Profession and understood about DaGuSiBu (properly get, use, save, and throw away the medicines) with the results of the average pretest and posttest scores about Pharmacist of 7.08 and 7.23 respectively, meanwhile DaGuSiBu education was 6.20 for pretest and postest 7.18. So it can be concluded that there was increasing points in knowledge after being given education.